Венгры и Русь в Поднепровье - Петрухин, B.Я. (Хазарский альманах, 2009)
В статье сопоставпены сведения источников о времени и обстоятельствах появления венгров в Поднепровье с данными о переселении летописной руси в Киев. В результате, автору статьи удалось прийти к выводу, что в IX в. русь осваивала путь через Восточную Европу с севера на юг, а кочевники-венгры — с востока на запад. Поэтому и те, и другие были включены в геополитическую систему отношений “великих держав" раннего Средневековья. У статті зіставлені свідчення джерел про час і обставини появи угорців у Подніпров’ї з даними про переселення літописної русі в Київ. У результаті, автору статті удалося прийти до висновку, що в IX ст. русь освоювала шлях через Східну Європу з півночі на південь, а кочівники-угорці — зі сходу на захід. Тому і ті, й інші були включені в геополітичну систему відносин "великих держав” раннього Середньовіччя. In this paper the evidences of written sources on the time and circumstances of appearing of the Hungarians in the Dniper basin and also data on the migration of the Rus' to Kiev are compared. As a result, the author of this research made the conclusion that in IX century AD the Rus’ assimilated the road across the Eastern Europe from the North to South and the Nomadic Hungarians assimilated the road from the East to West one as well. Therefore the firsts and others were included into the Geopolitical system of relationships of the early medieval "Great States”.